PENERAPAN METODE FUZZY TSUKAMOTO & DECISION TREE C4.5 PADA SISTEM PAKAR UNTUK DIAGNOSIS PENYAKIT GASTROESOPHAGEAL REFLUX PADA LAMBUNG - Githa Oktaviani; Albaar Rubhasy (Journal of Research and Publication Innovation, 2024)
Githa Oktaviani, 207064416062, Informatics Study Program. Lack of public knowledge about GERD, starting from the assumption that GERD is a deadly disease to the assumption that GERD arises from the sufferer's excessive feelings about something is one of the main factors that causes the wrong treatment of GERD disease. So that an expert system for GERD diagnosis is needed to provide information to the public about GERD and its symptoms. This study aims to develop an application that can help doctors and patients in diagnosing GERD stomach disease more quickly and accurately using the Fuzzy Tsukamoto algorithm and Decision Tree C4.5. This application is expected to overcome the problem of complications that arise due to improper and slow treatment of GERD disease. This application is made for the web using the PHP programming language and MySQL database. From 38 test data, the accuracy level reached 89.47% for the fuzzy tsukamoto method, while the decision tree method produced an accuracy of 92.69%.